Predicting oral hygiene practices through health behavior, perceived stress and self-efficacy in undergraduate dental students of Pakistan: a national survey - Khaloud Tariq; Sadia Shakeel; Ambrina Qureshi; Javaid Unar; Areeba Qamar; Athar Khan (BMC, 2024)
Abstract Background Dental students face the rigorous demands of coursework, which can lead to feelings of inadequacy and stress. These pressures can negatively influence self-efficacy and cause neglect in practicing healthy behaviors that encompass oral health. Identifying the associations of these variables with oral hygiene practices can help in the formulation of interventions tailored toward supporting young students. Therefore, this study aimed to investigate the impact of health behaviors, perceived stress and self-efficacy on oral hygiene practices among undergraduate dental students in Pakistan. Methods A national online survey was carried out among 904 students across the dental colleges of Pakistan. The survey assessed general health behaviors such as tobacco use, sleep, and exercise, among other demographic variables. Perceived stress was evaluated via the Perceived Stress Scale (PSS-10), and self-efficacy was evaluated via the General Self-Efficacy Scale (GSES). Twice daily brushing, brushing for 2 min, and changing toothbrushes after 3 months informed oral hygiene practice of the participants. Results The students experienced moderate perceived stress (20.82 ± 5.92) and high self-efficacy (29.19 ± 5.43). The majority of participants were in their third year (31.9%), were female (65.9%), and resided in home during their studies (64.4%). Perceived stress was observed to have no significant effect on the oral practice of participants. Female gender, non tobacco user, regular exercise, frequent dental visits and higher self-efficacy were associated with good oral hygiene practices. Conclusions The results highlight the importance of addressing stress, enhancing self-efficacy and encouraging healthy behaviors among dental students to improve their oral health, which could be reflected in their professional practice and personal well-being. This study contributes to the understanding of behavioral determinants and emphasizes the need for supportive measures to foster better health behaviors in future dental professionals.